Sol-gel route to carbon nanotube borosilicate glass composites - Thomas, Boris J. C.; Shaffer, Milo S. P.; Boccaccini, Aldo R. (Composites Part A-Applied Science and Manufacturing, 2009)
Dense borosilicate glass matrix composites containing up to 3 wt% of multiwalled carbon nanotubes were produced by a sol-gel process. The three different silicate precursors employed (tetramethylsilane (TMOS), methyltriethoxysilane (MTES) and methyltrimethoxysilane (MTMS)) yielded transparent xerogels which were subsequently crushed and densified by hot pressing at 800 °C. The dispersion of the carbon nanotubes was aided by using an organic-inorganic binder (3-aminopropyl triethoxysilane) which limited flocculation of the CNTs in the silica sol. After densification, the borosilicate glass composites containing up to 2 wt% CNTs showed significant improvements in hardness and compression strength, as well as thermal conductivity, whilst percolation effects lead to a dramatic increase in electrical conductivity above 1 wt%. This simple approach to disperse CNTs into a technical silicate glass matrix via the sol-gel process focusses specifically on the borosilicate system, but the procedure can be applied to produce other inorganic matrix composites containing CNTs. © 2009 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.tech.IW.LM.solgel
Keywords: A. Ceramic-matrix composites (CMCs); A. Glasses; B. Mechanical properties; D. Thermal analysis